2001
DOI: 10.1074/jbc.m009216200
|View full text |Cite
|
Sign up to set email alerts
|

Cytosine Methylation Enhances Mitoxantrone-DNA Adduct Formation at CpG Dinucleotides

Abstract: Recently, we have shown that mitoxantrone can be activated by formaldehyde in vitro to form DNA adducts that are specific for CpG and CpA sites in DNA. The CpG specificity of adduct formation prompted investigations into the effect of cytosine methylation (CpG) on adduct formation, since the majority of CpG dinucleotides in the mammalian genome are methylated and hypermethylation in subsets of genes is associated with various neoplasms. Upon methylation of a 512-base pair DNA fragment (containing the lac UV5 p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
26
0

Year Published

2003
2003
2023
2023

Publication Types

Select...
5
4

Relationship

4
5

Authors

Journals

citations
Cited by 25 publications
(26 citation statements)
references
References 17 publications
0
26
0
Order By: Relevance
“…8), and in a cellular environment, this may endow these adducts with the capacity to alter the expression of the genes in which they occur; this is presently under examination. Indeed, other CpG-specific alkylators, including formaldehyde-activated mitoxantrone, mitomycin C, and the carcinogen benzo(a)pyrene diolepoxide, are also enhanced by CpG methylation (Li et al, 2000;Parker et al, 2001).…”
Section: Discussionmentioning
confidence: 99%
“…8), and in a cellular environment, this may endow these adducts with the capacity to alter the expression of the genes in which they occur; this is presently under examination. Indeed, other CpG-specific alkylators, including formaldehyde-activated mitoxantrone, mitomycin C, and the carcinogen benzo(a)pyrene diolepoxide, are also enhanced by CpG methylation (Li et al, 2000;Parker et al, 2001).…”
Section: Discussionmentioning
confidence: 99%
“…It is known that mitoxantrone binds covalently to DNA specifically and preferentially at methylated CpG sites. 7 We predicted that higher the levels of methylated DNA in cells, the greater the mitoxantrone cytotoxicity. Conversely, reducing the level of methylation in cells would result in a lowered cytotoxicity of the drug.…”
Section: Reduced Levels Of Methylation In Cells Reduces Cytotoxicity Ofmentioning
confidence: 99%
“…4 In addition, mitoxantrone can also be activated by formaldehyde in cell-free systems to bind covalently to DNA, 5 specifically at CpG and CpA sequences in DNA, producing labile drug-DNA adducts which can be detected as 'virtual' interstrand crosslinks. 6 Further work revealed that drug binding was enhanced 3-fold when CpG sites in DNA were methylated 7 and that the cytotoxic effects of mitoxantrone are augmented by formaldehyde. AN-9 (pivaloyloxymethyl butyrate), a butyric acid prodrug, upon hydrolysis releases butyric acid, pivalic acid and formaldehyde.…”
Section: Introductionmentioning
confidence: 99%
“…22 The cytosine residue in CpG sequences (found disproportionately in regulatory promoter regions) is often methylated, with methylation typically occurring after DNA replication. A bis-amino mitoxantrone analogue, named herein WEHI-150 (see Figure 1), was synthesised in an attempt to develop anthracenedione analogues that are more reactive with DNA than mitoxantrone and pixantrone, but are also more likely to form covalent cross-links between the two DNA strands, through the formation of an adduct with a covalent bond to a guanine residue on each strand of the duplex.…”
Section: Introductionmentioning
confidence: 99%